Characteristics of Ethical Leadership: Themes Identification Through Convergent Parallel Mixed Method Design From the Pakistan Context - Shahab, Hina; Zahur, Hafsah; Akhtar, Naveed; Rashid, Sobia (Frontiers in Psychology, 2021)
The current approaches in identifying the characteristics of ethical leadership proceed mainly from a Western perspective based on virtue-driven moral philosophy (i.e., relativism) and frequently ignoring the Asian perspective of morality based on idealism. This study aimed to conduct parallel analysis in convergent design by using qualitative and quantitative methods to extract person-driven ethical leadership themes by considering the Asian context. Using the hypothetico-deductive method, thirteen themes were extracted altogether, out of which four new context-driven themes (i.e., altruism, encouragement, collective good and spiritual transcendence as the emerging themes of ethical leadership in the Asian context).